Message Analysis in The Film “Jodoh 3 Bujang” - Dahniar Niar; Ken Amasita Saadjad; Mohamand Rizky; Wanda Ramadhani Ibrahim (Jogjakarta Communication Conference (JCC), 2026)
This study aims to analyze the moral, social, and cultural messages in the film Jodoh 3 Bujang (Three Bachelors' Destiny), which features Bugis-Makassar traditions such as uang panai (bride price), twin marriages, siri’ (dignity/honor), and arranged marriage. Using a qualitative descriptive research method, the analysis is carried out through observation of scenes, dialogues, and visual symbols, as well as applying Roland Barthes' semiotic theory to examine how the film shapes meaning and audience perception. The results show that the film contains important messages about customs, the importance of family communication, sibling solidarity, and efforts to maintain dignity amid modernity. The comedic elements make the delivery of these messages lighter and easier to understand, so the film not only entertains but also increases understanding of cultural values and encourages audiences to reflect on the relevance of traditions today.